Uncovering doctors’ perceived barriers and facilitators of antibiotic prescribing behaviours: a qualitative study using the theoretical domains framework - Acampora, Marta; Guasconi, Massimo; Schiroli, Chiara; Coschignano, Cristina; Cassinari, Nicole; Cipolla, Rosalba; Artioli, Giovanna; Bonacaro, Antonio; Sarli, Leopoldo; Barello, Serena (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: Uncovering the barriers and facilitators of antibiotic prescribing is crucial in order to develop effective strategies for promoting responsible and evidence-based antibiotic use, thereby combating antibiotic resistance and enhancing patient care. This qualitative study, informed by the Theoretical Domains Framework (TDF) – specifically designed to understand and analyze the factors that influence human behavior, with a focus on identifying barriers and facilitators to behavior change, was aimed to explore the determinants (barriers and facilitators) of antibiotic prescribing behaviors from the perspective of doctors. Research design and methods: Semi-structured interviews were conducted with healthcare professionals, and data analysis followed a theory-driven approach guided by the TDF. Results: The analysis identified eight TDF domains influencing antibiotic prescribing, including memory, attention, and decision processes; knowledge; skills; belief about capabilities; goals; belief about consequences; emotions; and environmental context and resources. These domains were clustered into three overarching themes according to a bottom-up logic: the decision-making prescribing process itself, intrinsic factors related to the physician, and extrinsic factors influencing the decision. Conclusions: This research provides a comprehensive understanding of the complex interactions between these determinants in antibiotic prescribing. The evidence gained from the study valuable information for developing targeted interventions to improve antibiotic prescribing practices and combat antimicrobial resistance considering psychosocial and environmental variables impacting on antibiotic prescription decision making.